Influenza Viral Infections Surveillance and Clinical Presentations in Hospitalized Children: A Cross-sectional Study - Al-Iede, Montaha; Sarhan, Lena; Abushanab, Leen; BaniAhmad, Tamara; Almiani, Refa; Alyasi, Aysha; Khader, Shatha; Aleidi, Shereen M.; Alqutawneh, Basim; Al-Zayadneh, Enas (Current Respiratory Medicine Reviews, 2021)
Background: Influenza virus and other respiratory viruses have been identified as an essential cause of acute respiratory infections (ARIs) in children worldwide. However, there are few data on its frequency and clinical presentation in Jordan. Objectives: We aimed to identify the viral etiology of acute respiratory infections and the various clinical presentations in hospitalized children, especially those with influenza viruses compared to other respiratory viruses. Methods: A retrospective study was conducted at the Jordan University Hospital. All the positive nasopharyngeal aspirates that were collected from hospitalized children aged 0-19 years from January 2017 to January 2019 were reviewed. Results: A total of 338 nasopharyngeal aspirates (NPAs) with positive viral serology results were reviewed. Among the patients younger than four years, the RSV virus was the most frequently detected. However, the Influenza B virus was the most commonly seen in patients older than 5 years, H1N1 was more frequent in autumn (29.5%), and RSV was the most frequent virus in winter. Bronchopneumonia was the most frequent diagnosis among all hospitalized patients, followed by bronchiolitis. Out of 338 patients, 50.3% had tachypnea, 70.7% of patients were admitted to the pediatric floor, while 18.6% presented with a severe illness and required admission to the pediatric intensive care unit (PICU). Infants under the age of one were more likely to have higher co-infection rates with other viruses compared to children over five years that had influenza. Conclusion: Presentations of influenza and other respiratory viruses vary between different age groups, such as sepsis in children younger than one year.
Keywords: clinical presentation